PEER GROUP SUPPORT EFFECTIVITY TOWARD THE QUALITY OF LIFE AMONG PULMONARY TUBERCULOSIS AND CHRONIC DISEASE CLIENT : A LITERATURE REVIEW - Alfid Tri Afandi (NurseLine Journal, 2016)
Tuberculosis (TB) is one of the major infectious diseases in the world. There were 10.4 million new tuberculosis cases in 2015 and the number of deaths reached 1.4 million. This literature review described the effectiveness of peer group support to improve the quality of life of clients especially with pulmonary tuberculosis and other chronic diseases. This literature review used 25 electronic journals from over 100 international and national electronic journals published between 2006 and 2016, with the inclusion criteria of studies using peer group support treatment, tuberculosis disease and other chronic diseases treated with peer group support.The exclusion criteria is research using group method, but there was no resemblance due to illnes among client that follow the group method. Keywords used to find the journals were peer group support for pulmonary tuberculosis and “dukungan sebaya terhadap klien dengan tuberkulosis paru”. Search engines of this study were Google search, PNRI (Perpustakaan Nasional Republik Indonesia) and Master journals. Twenty five journals used in this literature review concluded that peer group support can improve quality of life of clients with pulmonary tuberculosis and other chronic diseases such as diabetes mellitus and HIV-AIDS, but some conditions need additional therapy to be more optimal. Peer group support can improve quality of life of TB clients and can be recommended as a variety of nursing interventions in controlling pulmonary tuberculosis